Intelligent computer mathematics : 9th International Conference, CICM 2016, Bialystok, Poland, July 25-29, 2016. Proceedings /: 9th International Conference, CICM 2016, Bialystok, Poland, July 25-29, 2016. Proceedings. (2016) - Unknown
No abstract available